Intra-Religious Exclusivism among Indonesia’s Hijra Communities: Identity Construction and the Marginalization of Muslim Others - Fathiyaturrahmah, Fathiyaturrahmah; Edi Wibowo, Safrudin; Ashfiya, Za‘imatil (Universitas Muhammadiyah Yogyakarta, 2025)
The increasing trend of hijra has given rise to the phenomenon of religious exclusivism among the Hijra Community members in Indonesia. This trend of religious exclusivism raises concerns about the development of radical Islam and intolerance towards Muslim others. This research aimed to explore intra-religious exclusivism of the Hijra Community members, i.e., Majelis Gaul, Sahabat Al-Qur’an, Al-Fath Pemuda Hijrah, and Komunitas Hijrah Jember (KHJ). This research also analyzed the factors that influence exclusivism and their implications for relations with Muslims others. This research collected data through observation, in-depth interviews, and documentation. The collected data were analyzed using three steps: data reduction, data display, and inference. The findings of this research showed that the exclusivism of members of the hijra community varied from open and closed to extreme exclusivism. Furthermore, the factors that influenced exclusivism were the high religious spirit after hijra, religious understanding that introduced only a single truth, family background, religious organizations, and the influence of religious figures to whom they referred. We found that religious exclusivism implied three models of othering practices toward Muslim others: isolationism, persistence in the community with their views, and persistence in their community but tolerating differences in understanding